USING ONE STAY TWO STRAYS TOWARD STUDENTS’ READING COMPREHENSION AND PARTICIPATION OF NARRATIVE TEXT - ERIPUDDIN (English Study Program University of Pasir Pengaraian, 2015)
The purposes of this research were to find out effect of OSTS strategy on students reading comprehension and students’ participation. There are four hypotheses formulated, First, There is no significant difference on the students’ reading comprehension pre-test mean score between experimental group and control group. Second, there is no significant difference on the students’ reading comprehension posttest mean score between experimental group and control group. Third, there is no significant different on the students’ reading comprehension pre-test and post-test mean score of the experimental group. Fourth, there is no significant different on the students’ participation in teaching and learning reading comprehension of experimental group before and after using one stay two strays strategy. The population was the grade X SMAN 2 Rambah Hilir. There are 4 classes. By using cluster random sampling, it was found that X C as try out class, X B as experimental class and X A as the control. This research was conducted by using quasi experiment. The researcher used test as the instrument and analyzed by using T-test. The result shows that one stay two strays could improve students’ reading comprehension and participation.